Mechanical Engineering Tables and Charts (SI Units) (Manila, Philippines : Manila Review Institute, Inc., 2004)
This edition has includes new material to increase the sphere of usefulness of the manual as reference to anyone engaged in mechanical engineering practice.
Steam Tables -- Refrigerant Tables and Charts -- Absorption Solution -- Air Tables -- Conditioning Tables -- Gas Tables -- Storage Design Data -- Fluid Flow -- Pump Selection -- Hydraulic Turbine Selection Charts .
Includes bibliographical references.
Keywords: MECHANICAL ENGINEERING